A Study on Customer Satisfaction Towards Allen Solly Apparels in Ahmedabad City - Oza, Lipi; Shah, Sameer; Vidani, Jignesh (MultiTech Publisher, 2024)
This research investigates the level of customer satisfaction with Allen Solly apparels in Ahmedabad city with the aim to provide some valuable insights of components influencing customer preferences in the competitive apparel market. The used quantitative research method to gather the data from a diverse sample of Allen Solly customers in Ahmedabad. The research objectives includes evaluating customer satisfaction, identifying factors influencing purchasing decisions, assessing how the customer service is effective, and understanding viewpoint of product quality and brand name. The survey instruments includes Likert – scale questions to collect quantitative aspects of customer satisfaction. The findings of this research concludes the strengths and weaknesses of Allen Solly in Ahmedabad City. Moreover, the research aims to provide implementable suggestions for the company to improve customer satisfaction, loyalty, and competitiveness in the evolving retail environment. This study serves as an essential reference for researchers, professionals, and shareholders interested in understanding consumer behaviour and improving strategies